2019
DOI: 10.1002/cpe.5448
|View full text |Cite
|
Sign up to set email alerts
|

JPEG steganography with particle swarm optimization accelerated by AVX

Abstract: Summary Digital steganography aims at hiding secret messages in digital data transmitted over insecure channels. The JPEG format is prevalent in digital communication, and images are often used as cover objects in digital steganography. Optimization methods can improve the properties of images with embedded secret but introduce additional computational complexity to their processing. AVX instructions available in modern CPUs are, in this work, used to accelerate data parallel operations that are part of image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The test file used for the following benchmark is available online (https://gitlab.inria.fr/bramas/arm-sve-sort) and includes the different sorts presented in this study plus some additional strategies and tests. 4 Our QS uses a 5-values median pivot selection (whereas the STL sort function uses a 3-values median). The arrays to sort are populated with randomly generated values.…”
Section: Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…The test file used for the following benchmark is available online (https://gitlab.inria.fr/bramas/arm-sve-sort) and includes the different sorts presented in this study plus some additional strategies and tests. 4 Our QS uses a 5-values median pivot selection (whereas the STL sort function uses a 3-values median). The arrays to sort are populated with randomly generated values.…”
Section: Configurationmentioning
confidence: 99%
“…Sorting is a fundamental problem in computer science and a critical building block for many types of applications such as, but not limited to, database servers [1], image rendering engines [2], mining of time series [3] or JPEG steganography with particle swarm [4]. This is why sorting algorithms have the attention of the research community intending to provide efficient sorting libraries on new architectures that could potentially leverage the performance of a wide range of software.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Particle Swarm Optimization (PSO) has also enjoyed considerable success in the literature. Li et al [16], Snasel et al [17], Fazli et al [18] and Rabevohitra and Sung [19] have all found success applying PSO to design custom quantization tables to improve the quality of hidden messages in steganography. On its turn, Ma and Zhang [20] have suggested a cultural-based multi-objective PSO algorithm for choosing the quantization tables, establishing a pareto front of possible quantization tables, achieving a significant visual enhancement, despite the fact that no evaluation was provided.…”
Section: Related Workmentioning
confidence: 99%
“…The paper entitled “JPEG Steganography with Particle Swarm Optimization Accelerated by AVX” by V. Snasel, P. Kromer, J. Safarik, and J. Platos presents new digital steganography aspects. These types of steganography aim at hiding secret data in digital form transmitted over insecure channels.…”
Section: The Main Topics Of Coginnov 2018 Special Issuementioning
confidence: 99%